Impact of age on short-term outcomes after pancreaticoduodenectomy: A retrospective case-control study of 260 patients - Zhao, Zhirong; Zhou, Shibo; Tang, Yaping; Zhou, Lichen; Ji, Hua; Tang, Zheng; Dai, Ruiwu (Frontiers in Surgery, 2023)
Background: Although the increase of perioperative complications in the elderly undergoing pancreaticoduodenectomy (PD) surgery has been recognized, the definition of the “old patient” of PD in the studies is different and there is no accepted cut-off value at present. Methods: 279 consecutive patients who have undergone PD in our center between January 2012 and May 2020 were analyzed. Demographic features, clinical-pathological data and short-term outcomes were collected. The patients were divided into two groups, and the cut-off value (62.5 years) is picked based on the highest Youden Index. Primary endpoints were perioperative morbidity and mortality, and complications were classified according to the Clavien-Dindo Score. Results: A total of 260 patients with PD were included in this study. Postoperative pathology confirmed pancreatic tumors in 62 patients, bile duct tumor in 105, duodenal tumor in 90, and others in 3. Age (OR = 1.09, P <0.01), and albumin (OR = 0.34, P <0.05) were significantly correlated with postoperative Clavien-Dindo Score≥3b. There were 173 (66.5%) patients in the younger group (<62.5 years) and 87 (33.5%) in the elderly group (≥62.5 years). Significant difference between two groups was demonstrated for Clavien-Dindo Score ≥3b (P<0.01), postoperative pancreatic fistula (P<0.05), and perioperative deceases (P<0.05). Conclusions: Age and albumin were significantly correlated with postoperative Clavien-Dindo Score ≥3b, and there was no significant difference in predicting the grade of Clavien-Dindo Score. The cut-off value of elderly patients with PD was 62.5 years old and there were useful in predicting Clavien-Dindo Score ≥3b, pancreatic fistula, and perioperative death.